Application of the Health Belief Model on the Reproductive Health Services Uptake in Adolescents: A Meta-Analysis - Dyah Ayu Kusumawardani; Elsa Jumasni Ayu (Journal of Health Promotion and Behavior, 2021)
Background: Adolescence is a period of transition from childhood to adulthood and is characterized by changes in physical, psychological, and social behavior that can affect their lives at high risk. Various problems that occur in adolescents are influenced by various dimensions of life within them, both biological, cognitive, moral and psychological dimensions as well as the influence of the surrounding environment. This study aimed to estimate the effect of the Health Belief Model, especially its construction of perceived vulnerability, perceived seriousness, and perceived benefits in the use of reproductive health services with a meta-analysis.Subjects and Method: This study is a review of meta-analytical studies. This research article was obtained from the electronic databases of PubMed, Springer Link, Elsevier and Google Scholar. The articles used in this study are articles published from 2011-2021. The search for articles was carried out by considering the eligibility criteria defined using the PICO model. P: adolescents. I: perceived vulnerability, perceived seriousness, perceived benefit. C: Low perceived vulnerability, perceived seriousness, perceived benefit. O: use of reproductive health services. The articles included in this study are full text articles with a Srocsectional study design. This article was analyzed using the Review Manager 5.3 application.Results: There are 9 articles in total. The results showed that there was high heterogeneity (I2= 82%; p <0.0001), so that the data analysis on the florest plot used a random effect model. The perception of vulnerability that is felt to be strong increases the likelihood of using reproductive health services by 2.42 times compared to the perception of vulnerability that is felt to be weak, and it is not statistically significant (aOR= 2.42; 95% CI= 1.60-3.67; p= 0.001).Conclusion: The use of reproductive health services is not statistically significant in predicting reproductive health in adolescents.Keywords: health belief model, belief, reproductive health service, reproductive health careCorrespondence:Dyah Ayu Kusumawardani. Universitas Muhammadiyah Surakarta, Central Java, Indonesia. Email: dijeayu16@gmail.com. Mobile: +6281466847498.Journal of Health Promotion and Behavior (2021), 06(04): 318-326DOI: https://doi.org/10.26911/thejhpb.2021.06.04.06